Study of damping effect on CMOS-MEMS resonator for biomarker detection in exhaled breath - Rabih, A.A.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
CMOS-MEMS resonators have found a broad usage in mass sensing applications. They can be used to detect biomarkers in exhaled breath (EB) for screening of diseases. Damping is believed to hinder the performance of these resonators. This paper focuses on investigating effects of damping in natural frequency, mass sensitivity and displacement of a proposed resonator for biomarker detection in EB. The resonator is electrostatically actuated using parallel plate capacitor principle. Squeeze film damping was found to affect the resonator performance when the gap distance between the plates was varied as 5, 7, 9, 10 and 11 μm, in which 5 μm led the resonator to be overdamped. For the rest of gaps the resonator is underdamped. FEA simulation using CoventorWare was used to confirm the mathematical modeling of the resonator, in which results agree with the modeling within an acceptable percentage error of 5 . © 2016 IEEE.